Thực trạng và một số giải pháp phát triển năng lực quản trị đại học cho viên chức quản lí tại Trường Đại học Đồng Tháp - Trương , Tấn Đạt; Bùi , Văn Diễn (Tạp chí Giáo dục, 2022)
The higher education system in Vietnam has undergone fundamental and comprehensive changes, especially the increase of autonomy and accountability, the diversification of ownership of universities; the matter of “marketing” in higher education, etc. These problems have made university administration activities with the traditional methods no longer suitable and led to a gradual shift to the university governance. The article examines the current situation of developing university administration capacity for management staff at Dong Thap University in the following aspects: planning; training and retraining; developing university administration capacity for managerial staff and evaluating the effectiveness of this process. Based on the survey results, the article proposes a number of solutions to develop university administration capacity for university management staff. It is revealed that, university governance is a new approach, requiring senior administrators and other members of the university at the middle and low levels participating in the management of “stages and processes” of university operation to be equipped with essential competencies, at least in terms of university governance.